Strengthened impairment argument does not restate Marquis - Blackshaw, Bruce Philip (2021)
With Perry Hendricks, I recently outlined a strengthened version of the impairment argument (SIA) for the immorality of abortion. Alex Gillham has argued that our use of Don Marquis’ deprivation of a ‘future-like ours’ account entails we were merely restating Marquis’ argument for the immorality of abortion. Here, I explain why SIA is more than just a reframing of Marquis.